General chemistry:Supplement sampler to accompany - Umland, Jean B. (New York West Group, 1993)
For students to learn to think scientifically, they need something to think about. Authors Jean B. Umland and Jon M. Bellama accomplish this by integrating descriptive chemistry and theory throughout the book. From the very first chapter, the authors familiarize students with chemical reactions - which Umland and Bellama believe are the heart of chemistry. But the authors go beyond describing what happens during a reaction to explaining WHY chemical reactions occur. This allows the first lectures to include the interesting demonstrations that capture student interest and keep them captivated throughout the course. It's this approach that helps involve students in a fascinating discovery process that lets them experience the "Aha!" feeling, and makes them eager to learn more about the chemical processes taking place around them.
Keywords: Chemistry,general chemistry